Preferensi Penggunaan Material pada Atap Rumah Tinggal - Dindha Nirmalasari; Irma Handayani Lubis; Hanson Endra Kusuma; Mochamad Donny Koerniawan (Tesa Arsitektur, 2020)
Roof material preferences for housing can be influenced from the location of the respondents, local climate, culture, knowledge and comfortable condition of the occupants. The aim of this research is to get the reasons behind the selection of roof material for housing. Quantitative method is used in this research by collecting data of online questionnaire. This online questionnaire is distributed using convenient sampling method (snowball-non-random-sampling). It was found the tendency of respondents who choose clay tile because of the comfort and affordability of the price. The tendency of respondents who choose ceramic tile and natural wood tile because of their beauty and sustaniability materials. Concrete is selected by respondents because of their durability and strength. Respondents who have tendency in Zinc, asbestos are selected because zinc and asbestos are easy to apply and commonly materials in their areas. Asphalt, metal, and PVC / galvalum / fiber are chosen by respondents for being lightweight materials.